2008
DOI: 10.1093/jee/101.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Kaolin Affects Blueberry Maggot Behavior on Fruit

Abstract: This study assessed the effects of Surround (kaolin) on several behavioral parameters of female blueberry maggot, Rhagoletis mendax Curran (Diptera: Tephritidae). First fruit visited, walking, cleaning, and oviposition behavior were quantified in two-choice and no-choice assays where females encountered Surround-treated and untreated fruit of highbush blueberries (Vaccinium spp.). In two-choice assays, females had a propensity (68%) to first visit untreated blueberries. In two-choice and no-choice tests, numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 0 publications
2
19
0
3
Order By: Relevance
“…Particle films also suppresses insect pests by repellency, impeding egg laying, reducing feeding, impeding grasping, restricting their movement, behavior alteration, paralysis induction and by causing mortality Puterka et al, 2000b). The mechanisms underlying how particle films affect the biology and behavior of insect pests have been extensively explored by several authors (Cadogan and Scharbach, 2005;Puterka et al, 2005;Lemoyne et al, 2008), describing a variety of effects i.e., direct toxicity and interference with insects ability to settle, move or oviposit (Hall et al, 2007). Porcel et al (2011) studied the biological and behavioral effects of a kaolin particle film on larvae and adults of Chrysoperla carnea Stephens and found that a higher number of C. carnea adults were found associated with kaolin treated olive trees which indicate that, disruption of movement capacity and dislodgment from the plant surface may be the main negative actions of particle films on C. carnea larvae while adults showed a positive trend in oviposition and abundance towards kaolin treated surfaces.…”
Section: Insect Pest Damagementioning
confidence: 99%
“…Particle films also suppresses insect pests by repellency, impeding egg laying, reducing feeding, impeding grasping, restricting their movement, behavior alteration, paralysis induction and by causing mortality Puterka et al, 2000b). The mechanisms underlying how particle films affect the biology and behavior of insect pests have been extensively explored by several authors (Cadogan and Scharbach, 2005;Puterka et al, 2005;Lemoyne et al, 2008), describing a variety of effects i.e., direct toxicity and interference with insects ability to settle, move or oviposit (Hall et al, 2007). Porcel et al (2011) studied the biological and behavioral effects of a kaolin particle film on larvae and adults of Chrysoperla carnea Stephens and found that a higher number of C. carnea adults were found associated with kaolin treated olive trees which indicate that, disruption of movement capacity and dislodgment from the plant surface may be the main negative actions of particle films on C. carnea larvae while adults showed a positive trend in oviposition and abundance towards kaolin treated surfaces.…”
Section: Insect Pest Damagementioning
confidence: 99%
“…2003; Mazor and Erez 2003; Saour and Makee 2004; Braham et al. 2007; Caleca and Rizzo 2007; Villanueva and Walgenbach 2007; Lemoyne et al. 2008; Yee 2008).…”
Section: Introductionmentioning
confidence: 98%
“…2005). The adherence of kaolin to the insect could cause excessive grooming, interfere with grasping of plant surfaces, and reduce oviposition by preventing recognition of host surface chemicals (Lemoyne et al. 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Com este mesmo propósito, alguns trabalhos também relataram o uso de calcário líquido (carbonato de cálcio, Eclipse e Purshade) (Yee 2010;PraGer et al 2013). Esses produtos apresentaram bons resultados no controle da infestação de diversas espécies de tefritídeos, conhecidas como moscas-das-frutas (Mazor & erez 2004;Saour & Makee 2004;BrahaM et al 2007;leMoYne et al 2008;lo Verde et al 2011). De acordo com esses autores, a película branca formada por esses minerais sobre as superfícies das folhas, caules e frutos pode mascarar a cor das mesmas, dificultando, a longa distância, o reconhecimento do hospedeiro e também tornando a superfície do fruto áspera e menos adequada para oviposição, causando repelência.…”
unclassified